Visualization of Latent Fingermarks by Nanotechnology: Reversed Development on Paper-A Remedy to the Variation in Sweat Composition. - Jaber, Nimer; Lesniewski, Adam; Gabizon, Hadar; Shenawi, Sanaa; Mandler, Daniel; Almog, Joseph. (Angew. Chem., Int. Ed.Angewandte Chemie, International Edition, 2012)
In this work, "neg." fingermarks have been developed on paper, even after soaking in water, by the application of a new bifunctional reagent attached to gold nanoparticles, and then a silver phys. developer. The bifunctional reagent is composed of an active head, i.e., a polar group with high affinity to cellulose, attached by a long chain to an active tail contg. a sulfur group, which can stabilize gold nanoparticles. Through the active head, the gold nanoparticles, which are stabilized by the active tail, adhere preferentially to the paper cellulose rather than to the fingerprint material, to which they conventionally bind. Consequently, silver developer, which normally develops sebaceous fingermarks by pptg. dark silver on the sebaceous material, ppt. preferentially on the gold-coated areas giving rise to the appearance of uncolored ridge detail on a dark background. In this competing process, the paper itself serves as the substrate, whereas the fingermarks serve as a mask. This process may increase the overall yield of developed fingermarks as it bypasses the issue of the remarkable differences in sweat compn. between individual persons. [on SciFinder(R)]
CAPLUS AN 2012:1623037(Journal)
Keywords: forensic analysis latent fingerprint paper sweat gold nanoparticle silver